2021
DOI: 10.1002/ange.202108283
|View full text |Cite
|
Sign up to set email alerts
|

Fused‐Nonacyclic Multi‐Resonance Delayed Fluorescence Emitter Based on Ladder‐Thiaborin Exhibiting Narrowband Sky‐Blue Emission with Accelerated Reverse Intersystem Crossing

Abstract: Developing organic luminophores with unique capability of strong narrowband emission is both crucial and challenging for the further advancement of organic lightemitting diodes (OLEDs). Herein, a nanographitic fusednonacyclic p-system (BSBS-N1), which was strategically embedded with multiple boron, nitrogen, and sulfur atoms, was developed as a new multi-resonance thermally activated delayed fluorescence (MR-TADF) emitter. Narrowband skyblue emission with a peak at 478 nm, full width at half maximum of 24 nm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…One of the main strategies which can be used to accelerate RISC rate is to provide a high density of close lying 3 CT states, which can be achieved through peripheral substitution [30] . Alternatively the inclusion of heavy main group atoms such as S or Se to the molecular skeleton can be considered [31] . Finally, the inclusion of heavy metals is a suitable strategy to increase SOC values and improve RISC rates in MR‐emitters, although this reduces the economic and ecological sustainability of the devices [32] …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the main strategies which can be used to accelerate RISC rate is to provide a high density of close lying 3 CT states, which can be achieved through peripheral substitution [30] . Alternatively the inclusion of heavy main group atoms such as S or Se to the molecular skeleton can be considered [31] . Finally, the inclusion of heavy metals is a suitable strategy to increase SOC values and improve RISC rates in MR‐emitters, although this reduces the economic and ecological sustainability of the devices [32] …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that increasing the molecular rigidity and suppressing large excited state structural changes represents an efficient approach to achieve high color purity [31] . Therefore, design strategies focused on rigidity of the scaffold have been implemented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the more important studies based on boron‐based core structures [ 2–19 ] suggested that the 5,9‐dioxa‐13bboranaphtho[3,2,1‐de]anthracene (DOBNA) is the one well‐known core for MR‐TADF emitters. It has a boron and oxygen‐based fused aromatic structure due to MR effect and rigid structural properties.…”
Section: Introductionmentioning
confidence: 99%